Estudio del turno óptimo de descorche en alcornocales andaluces - ALAEJOS GUTIÉRREZ, J; Torres Álvarez, E; SÁNCHEZ AUNIÓN, M F (V Congreso Forestal Español, 2009)
El calibre del corcho tiene una gran influencia sobre la calidad final del producto. La selvicultura de alcornocales permite obtener un determinado calibre del corcho alargando o acortando el turno de descorche. El objetivo de este trabajo es determinar el turno óptimo de descorche para alcanzar la mejor calidad de corcho posible en un alcornocal determinado. Para alcanzar este objetivo, se ha medido el crecimiento anual de corcho en muestras procedentes de la colección de corcho, o suberoteca, del Plan de Calas de la Consejería de Medio Ambiente de la Junta de Andalucía. Las muestras fueron seleccionadas aleatoriamente en proporción a los porcentajes de las diferentes calidades y calibres de cada monte descorchado. El espesor de los anillos de crecimiento se realizó mediante análisis de la imagen escaneada del corte transversal de las piezas de corcho. Se realizó un análisis de regresión entre la edad del corcho, como variable independiente, y el calibre como variable dependiente. La ecuación parabólica resultó ser el mejor modelo. Se determinaron los coeficientes del modelo para cada región de procedencia y clase de calibre final del corcho. Estos modelos permiten realizar proyecciones en el tiempo del calibre final del corcho y predicciones de del calibre del corcho a diferentes edades. La proyección del calibre del corcho a los 9, 10, 11 y 12 años permite estimar y comparar la calidad final del corcho en un mismo monte con diferentes turnos de descorche. En tales condiciones, es posible calcular el turno óptimo de descorche utilizando métodos de análisis financiero. En contra de una idea frecuentemente generalizada, en un porcentaje apreciable de montes no es necesario un alargamiento del turno de descorche para obtener un corcho de mayor calidad.
Keywords: Alcornoque; Andalucía; Corcho; crecimiento

Estudio del turno óptimo de descorche en alcornocales andaluces - ALAEJOS GUTIÉRREZ, J.; TORRES ÁLVAREZ, E.; SÁNCHEZ AUNIÓN, M. F. (V Congreso Forestal Español, 2009)
El calibre del corcho tiene una gran influencia sobre la calidad final del producto. La selvicultura de alcornocales permite obtener un determinado calibre del corcho alargando o acortando el turno de descorche. El objetivo de este trabajo es determinar el turno óptimo de descorche para alcanzar la mejor calidad de corcho posible en un alcornocal determinado. Para alcanzar este objetivo, se ha medido el crecimiento anual de corcho en muestras procedentes de la colección de corcho, o suberoteca, del Plan de Calas de la Consejería de Medio Ambiente de la Junta de Andalucía. Las muestras fueron seleccionadas aleatoriamente en proporción a los porcentajes de las diferentes calidades y calibres de cada monte descorchado. El espesor de los anillos de crecimiento se realizó mediante análisis de la imagen escaneada del corte transversal de las piezas de corcho. Se realizó un análisis de regresión entre la edad del corcho, como variable independiente, y el calibre como variable dependiente. La ecuación parabólica resultó ser el mejor modelo. Se determinaron los coeficientes del modelo para cada región de procedencia y clase de calibre final del corcho. Estos modelos permiten realizar proyecciones en el tiempo del calibre final del corcho y predicciones de del calibre del corcho a diferentes edades. La proyección del calibre del corcho a los 9, 10, 11 y 12 años permite estimar y comparar la calidad final del corcho en un mismo monte con diferentes turnos de descorche. En tales condiciones, es posible calcular el turno óptimo de descorche utilizando métodos de análisis financiero. En contra de una idea frecuentemente generalizada, en un porcentaje apreciable de montes no es necesario un alargamiento del turno de descorche para obtener un corcho de mayor calidad.
The following values have no corresponding Zotero field: periodical: V Congreso Forestal Español pub-location: Avila
Keywords: Alcornoque; Andalucía; Corcho; crecimiento

Selección de rodales selectos de alcornoque (Quercus suber) EN ANDALUCÍA Angel - Carrasco, Angel; Campayo, Pablo; Sanchez, Mª Felisa (III Congreso Forestal Español, 2001)
La Consejería de Medio Ambiente de la Junta de Andalucía, a través de la empresa pública EGMASA, como medio propio, ha desarrollado una metodología para evaluar la selección de rodales selectos de alcornoque (Quercus suber) en Andalucía. En primer lugar se consideran unos requisitos o criterios generales que debe cumplir una masa de alcornocal para poder optar a formar parte de la relación de rodales selectos. Los parámetros considerados son: Calidad productiva, Aislamiento, Pureza, Número de pies por hectárea y Estado sanitario, es decir, aquellos que mayor influencia genética van a tener sobre la calidad de las nuevas plantas de alcornoque. En segundo lugar, se hace una valoración de cada rodal. Para ello, se han definido unos índices de tal forma que el valor suma de estos sirve para diferenciar como mejores aquellos de mayor puntuación. Los índices definidos son: Indice de Calidad de Corcho, Índice Morfológico e Índice sanitario. La sumaserá el valor definitivo por el que se evalúa el rodal, considerándose como rodales selectos aquellos que superen el valor medio de cada Región de Procedencia
Keywords: Andalucía; calidad; Quercus suber; selecto

Selección de rodales selectos de alcornoque (Quercus suber) EN ANDALUCÍA Angel - Carrasco, Angel; Campayo, Pablo; Sanchez, Mª Felisa (III Congreso Forestal Español, 2001)
La Consejería de Medio Ambiente de la Junta de Andalucía, a través de la empresa pública EGMASA, como medio propio, ha desarrollado una metodología para evaluar la selección de rodales selectos de alcornoque (Quercus suber) en Andalucía. En primer lugar se consideran unos requisitos o criterios generales que debe cumplir una masa de alcornocal para poder optar a formar parte de la relación de rodales selectos. Los parámetros considerados son: Calidad productiva, Aislamiento, Pureza, Número de pies por hectárea y Estado sanitario, es decir, aquellos que mayor influencia genética van a tener sobre la calidad de las nuevas plantas de alcornoque. En segundo lugar, se hace una valoración de cada rodal. Para ello, se han definido unos índices de tal forma que el valor suma de estos sirve para diferenciar como mejores aquellos de mayor puntuación. Los índices definidos son: Indice de Calidad de Corcho, Índice Morfológico e Índice sanitario. La sumaserá el valor definitivo por el que se evalúa el rodal, considerándose como rodales selectos aquellos que superen el valor medio de cada Región de Procedencia
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Andalucía; calidad; Quercus suber; selecto

Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A V (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation

Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A. V. (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation

Plan de calas de corcho y establecimiento de rodales selectos de alcornoque en andalucía - Carrasco, Angel; BORRERO, GUMERSINDO; CAMPAYO, P.; RODRIGUEZ, M.; ÁLVAREZ, J. Ma; FARIÑA, J. Ma; E. TORRES; Privado, Consultor; La, C. I.; Manojo, D. E. L.; Madrid, D. E. Rosas (II Congreso Forestal Español, 1997)
Since 1995, the "Consejería de Medio Ambiente" of the "Junta de Andalucía" has been developping a "Cork samples Plan and Establishment of select "Areas" of the Quercus suber". This plan is intended to collect technical-scientifical information, used both for a better knowledge of the cork oak forests and their principal product, cork, as well as for the elaboration of a cork quality map of the Andalusian Community. They also provide cork- tree owners with information about the explotation quality, for which cork samples are taken both from cork trees and from cork-piles. Using the collected samples, once they are classified and analised in the laboratory, and according to the data collected in the field, quality reports on cork are effec~ll(lted for the owner. Subsequently, these samples are show in a permanent exposition in thejaboratorywhere buyers or any other person interested can obtain information about the quality offered in the different Andalusian forests. Since 1995, the obtained information is also being used, amplifying the data taken referent to select "areas" of the cork oak forests to be able to establish a select "areas" network of Quercus suber capable of producing high quality acorns.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: Andalucía; Cork; cork-oak; Quercus suber; Select "areas"

Plan de calas de corcho y establecimiento de rodales selectos de alcornoque en andalucía - Carrasco, Angel; BORRERO, GUMERSINDO; CAMPAYO, P; RODRIGUEZ, M; ÁLVAREZ, J.Ma; FARIÑA, J.Ma; E.TORRES; Privado, Consultor; La, C I; Manojo, D E L; Madrid, D E Rosas (II Congreso Forestal Español, 1997)
Since 1995, the "Consejería de Medio Ambiente" of the "Junta de Andalucía" has been developping a "Cork samples Plan and Establishment of select "Areas" of the Quercus suber". This plan is intended to collect technical-scientifical information, used both for a better knowledge of the cork oak forests and their principal product, cork, as well as for the elaboration of a cork quality map of the Andalusian Community. They also provide cork- tree owners with information about the explotation quality, for which cork samples are taken both from cork trees and from cork-piles. Using the collected samples, once they are classified and analised in the laboratory, and according to the data collected in the field, quality reports on cork are effec~ll(lted for the owner. Subsequently, these samples are show in a permanent exposition in thejaboratorywhere buyers or any other person interested can obtain information about the quality offered in the different Andalusian forests. Since 1995, the obtained information is also being used, amplifying the data taken referent to select "areas" of the cork oak forests to be able to establish a select "areas" network of Quercus suber capable of producing high quality acorns.
Keywords: Andalucía; Cork; cork-oak; Quercus suber; Select "areas"